Open Ecosystems: Ecology and Evolution Beyond the Forest Edge - Siebert, F. (African Biodiversity & Conservation, 2021)
Review of: William Bond. 2019, Oxford University Press, Great Clarendon Street, Oxford, OX2 6DP, UK 192 pages, Hardcover, Paperback, Ebook ISBN-13: 978-0198812456 DOI:10.1093/oso/9780198812456.001.0001 78 ( R 1 135, Hardcover); 85 ( R 1 240, Ebook); 46 ( R 660, Paperback)